A bibliometrics and visualization analysis of cannabidiol research from 2004 to 2021 - Liu, Liu; Liu, Jianxing; Zhao, Ming; Cai, Meiming; Lei, Fanzhang; Zeng, Xiaofeng; Zhu, Bofeng (Frontiers in Pharmacology, 2022)
Cannabidiol, a non-psychoactive component extracted from the plant cannabis sativa, has gained growing focus in recent years since its extensive pharmacology effects have been founded. The purpose of this study intends to reveal the hot spots and frontiers of cannabidiol research using bibliometric and data visualization methods. A total of 3,555 publications with 106,793 citations from 2004 to 2021 related to cannabidiol were retrieved in the Web of Science database, and the co-authorships, research categories, keyword bursts, and reference citations in the cannabidiol field were analyzed and visualized by VOSviewer and Citespace software. Great importance has been attached to the pharmacology or pharmacy values of cannabidiol, especially in the treatment of neuropsychiatric disorders, such as epilepsy, anxiety, and schizophrenia. The mechanisms or targets of the cannabidiol have attracted the extreme interest of the researchers, a variety of receptors including cannabinoids type 1, cannabinoids type 2, 5-hydroxytriptamine1A, and G protein-coupled receptor 55 were involved in the pharmacology effects of cannabidiol. Moreover, the latest developed topic has focused on the positive effects of cannabidiol on substance use disorders. In conclusion, this study reveals the development and transformation of knowledge structures and research hotspots in the cannabidiol field from a bibliometric perspective, exploring the possible directions of future research.